The Impact Of Green Bond Issuance And ESG Performance On Firm Profitability: Evidence From Listed Companies In China, South Korea And Thailand - Kunto Adi Wicaksono (Cakrawala Repositori IMWI, 2023)
Concern on the detrimental effects of climate change is one reason for the increased global attention to sustainability issues. Significant investment is required to achieve carbon neutrality by 2050, and financing through green bonds is one alternative to fund green projects. On the other side, ESG criteria are frequently used as a measurement to assess corporations' commitment and actions toward net zero emission targets. However, whether the issuance of green bonds and ESG performance can increase profitability is still a big concern for companies. Using panel data from listed firms in China, South Korea, and Thailand from 2016 to 2022, this study employs the Difference-in-Difference (DID) model to investigate the impact of green bond issuance and ESG performance on firm profitability. Furthermore, panel data regression is used to examine the impact of green bond issuance on ESG performance. According to the findings of this study, the issuance of green bonds had no significant impact on ROA or ROE. However, according to the DID regression result, ESG performance (esg_1t) had a positive and significant effect on ROE (at a 10% significance level). This study also discovered that issuing green bonds (green_bond) had a negative and significant impact on the company's ESG performance.